2021
DOI: 10.1038/s41522-021-00205-8
|View full text |Cite
|
Sign up to set email alerts
|

Berberine attenuates choline-induced atherosclerosis by inhibiting trimethylamine and trimethylamine-N-oxide production via manipulating the gut microbiome

Abstract: Trimethylamine-N-oxide (TMAO), a derivative from the gut microbiota metabolite trimethylamine (TMA), has been identified to be an independent risk factor for promoting atherosclerosis. Evidences suggest that berberine (BBR) could be used to treat obesity, diabetes and atherosclerosis, however, its mechanism is not clear mainly because of its poor oral bioavailability. Here, we show that BBR attenuated TMA/TMAO production in the C57BL/6J and ApoE KO mice fed with choline-supplemented chow diet, and mitigated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 63 publications
(51 reference statements)
3
63
0
Order By: Relevance
“…This was accompanied by alterations in gut microbiota composition and function as well as altered cutC/cntA gene abundance. Data obtained from in vitro and fecal samples of choline-fed mice and human volunteers indicated that BBR inhibited the conversion of choline to TMA, and this conclusion was confirmed via transplantation of TMAproducing bacteria (including Anaerococcus hydrogenalis, Clostridium asparagiforme, Clostridium sporogenes, and Escherichia fergusonii) in mice (Li et al, 2021). These findings are also similar to those of our previous study on the effect of BBR on AS and gut microbiota regulation in HFD-fed ApoE −/− mice.…”
Section: Anti-atherosclerotic Effects Of Berberine Through the Regulation Of Gut Microbiota-dependent Metabolitessupporting
confidence: 88%
See 1 more Smart Citation
“…This was accompanied by alterations in gut microbiota composition and function as well as altered cutC/cntA gene abundance. Data obtained from in vitro and fecal samples of choline-fed mice and human volunteers indicated that BBR inhibited the conversion of choline to TMA, and this conclusion was confirmed via transplantation of TMAproducing bacteria (including Anaerococcus hydrogenalis, Clostridium asparagiforme, Clostridium sporogenes, and Escherichia fergusonii) in mice (Li et al, 2021). These findings are also similar to those of our previous study on the effect of BBR on AS and gut microbiota regulation in HFD-fed ApoE −/− mice.…”
Section: Anti-atherosclerotic Effects Of Berberine Through the Regulation Of Gut Microbiota-dependent Metabolitessupporting
confidence: 88%
“…Wang et al first demonstrated that 3,3-dimethyl-1-butanol (DMB, a choline structural analog), and its modified product could attenuate TMA formation non-lethally by inhibiting microbial TMA lyase (cutC and cutD), significantly reducing plasma TMAO levels and alleviating atherosclerotic lesions in diet-induced animal models (Wang et al, 2015;Roberts et al, 2018). A recent study published by Li et al (2021) further confirmed these results, as BBR was found to reduce TMA/TMAO production in choline-fed C57BL/6J and ApoE knockout mice and attenuate atherosclerotic lesion areas in the latter. This was accompanied by alterations in gut microbiota composition and function as well as altered cutC/cntA gene abundance.…”
Section: Anti-atherosclerotic Effects Of Berberine Through the Regulation Of Gut Microbiota-dependent Metabolitesmentioning
confidence: 99%
“…Some studies have demonstrated that knockdown of the FMO3 gene can significantly reduce the production of TMAO ( 67 , 68 ). In recent years, several new approaches have been found to inhibit the TMAO formation to alleviate the development of atherosclerosis ( 69 , 70 ). However, most researches conducted in vivo studies are in murine models, with few in humans.…”
Section: Metabolitementioning
confidence: 99%
“…A hypothesis regarding the potential capacity of berberine to modify gut microbiota and treat diabetes, obesity, and atherosclerosis was raised, based on the inhibition of TMA/TMAO production by gut microbiota mediated by berberine. According to the work of Li Xingxing et al, berberine proved to attenuate TMA/TMAO production, so it diminished atherosclerotic lesions in animal subjects fed with cereal-based diets, supplemented with choline [ 186 ].…”
Section: Pharmacological Approaches Impacting Microbiome Atherosclerosis and Vascular Calcificationsmentioning
confidence: 99%